Morgagni’s diaphragmatic hernia with Large ASD SECONDUM AND SEVER PHT mimicking a severe congenital heart disease in a newborn and cause delayed diagnosis of Morgagni’s diaphragmatic hernia . a case report - Khaleel , Huda (Jour Med Resh and Health Sci, 2022)
Morgagni hernia is a rare diaphragmatic hernia usually due to congenital defects in the diaphragm. It is rarely associated with cardiac anomalies, most commonly atrial small(ostium secundum) or ventricular septal defects. We report a rare case of Morgagni hernia occurring in association with Large ASD SECONDUM AND SEVER PHT mimicking a severe congenital heart disease in a newborn and the lack of awareness of the delayed presentation of Morgagni’s diaphragmatic hernia cause delayed of diagnosis clinical discussion: 0ur patients . an one month old girl , present with cyanosis and shortness of breath admitted were admitted with complaints of chronic cough and repeated chest infections treated accordingly and discharge in good condition .Readmitted after 1 week with similar presentation but her symptoms get worse by time ,patient admitted to PICU as aspiration Pneumonia, patient during the admission diagnosed with Congenital heart disease large ASD ( ostium secundum ) AND SEVER PHT,by echocardiography .she was stil lethargic hypotonic, low birthweight , she had intermittent cyanosis inspit treating the chest infection was investigated theoral, later she was diagnosed with Morgagni Hernia after repeating CT chest with contrast two times . Repair of hernia was done and out come was good inspite she was diagnosed late at age of 2 years. pulmonary hypertention treated ASD closure by double device Conclusion: Morgagni’s CDH is a rare malformation, which is difficult to diagnose by even the most experienced physicians. compression of the heart by the bowel might have led to the incorrect diagnosis of congenital heart disease. Even in this era of highly sophisticated diagnostic tools, A missed diagnosis can lead to life-threatening complications such as obstruction or strangulation which warrants early surgical intervention